Kapasitas Adsorpsi dan Efektivitas Karbon Aktif Pelepah Kelapa Sawit (Elaeis guineensis Jacq.) untuk Mengadsorpsi Ion Logam Tembaga (Cu2+) - Nurfatihayati, Nurfatihayati; Irianty, Rozanna Sri; Winarno, Winarno; Yani, Oktavia Dewa; Al'farisi, Cory Dian (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2025)
Palm fronds waste have a carbon content of 81.25%, which is quite high, making them suitable for use as activated carbon adsorbents that are beneficial for anticipating or minimizing the occurrence of Cu2+ ion pollution in the environment. This research aims to analyze the effect of contact time and mass of palm fronds activated carbon adsorbent on the adsorption of Cu2+ ions, the adsorption capacity of the palm fronds activated carbon adsorbent, and the effectiveness of the palm fronds activated carbon adsorbent in adsorbing Cu2+ ions. The research stages began with preparing palm frond samples with a size of (-80/+100) mesh, which was then activated with H3PO4 and 3M HCl for 24 hours. Based on the results, the best adsorbent characteristics used H3PO4 as the activator. The adsorption process was carried out with mass variations (10, 15, 20) g, contact times of (30, 60, 90, 120) minutes with a stirring speed of 90 rpm, and an adsorbate concentration of copper ions (Cu2+) of 10 mg/L. The optimal adsorption capacity obtained with the H3PO4 activator was at a contact time of 90 minutes with an adsorbent mass of 10 g, amounting to 0.965 mg/g. The highest adsorption effectiveness was found at a contact time of 90 minutes with an adsorbent amount of 20 g of palm frond activated carbon, which was 99.76%.